Early diagnostic ultrastructural features of Wilson’s disease - Zdravkovski, Panche; Petrushevska, Gordana (Taylor & Francis Online, 2017)
Wilson’s disease is an autosomal recessive genetic disorder of copper metabolism that is characterized by a defective incorporation of copper into ceruloplasmin. This leads to decreased excretion of copper and accumulation in excess in the liver, brain, and kidneys. Excess copper acts as a prooxidant and promotes generation of free radicals, leading to cell injury. We report a case with early ultrastructural characteristics. A 7-year-old female patient was admitted in the Pediatric Clinic because of abdominal pain and vomiting for a period of 5 days. Clinical examination showed palpatory firm and enlarged liver, 4 cm below the costal margin. Laboratory results showed elevated aminotransferases, low serum ceruloplasmin levels, negative serology for hepatotropic viruses, and absence of ophthalmologic symptoms. After the thorough examination, liver biopsy was done. Biopsy specimens were fixated in glutaraldehyde and embedded in Durcupan resin. Semi-thin sections dyed with Toluidine Blue and ultra-thin sections treated with uranyl acetate and lead citrate were made. Light-microscopic analysis of the semi-thin sections shows hepatic lobules with a moderate portal chronic inflammation and fibrosis. The trabecular architecture is disrupted as a result of fatty and parenchymal hepatocyte degeneration and focal piece-meal necrosis. There are evident apoptotic bodies and intranuclear glycogen inclusion. Electron-microscopic analysis of the ultra-thin sections shows degenerated hepatocytes, where the cytoplasm contains increased numbers of enlarged and relatively pleomorphic mitochondria with dilated cristae and intracristal spaces. Also, there is an increased number of peroxisomes, dilatation of smooth and rough endoplasmic reticulum, and neutral lipid vacuoles. There is discrete, plexiform electron-dense material in the cytosol of some hepatocytes located in the perinuclear and paranuclear regions, as well as in some mitochondria. Apart from the distinguishing ultrastructural features of the later symptomatic stage of Wilson’s disease (increased lipofuscin in pericanalicular regions, multivesiculated electron-dense copper deposits within the lysosomes, and finely granular hemosiderin electron densities), electron-microscopic analysis of an early stage disease can show only subtle and sometimes non-specific features. Nonetheless, transmission electron microscopy is a valuable diagnostic tool for this rare disease.
Keywords: Wilson; copper; ceruloplasmin; liver; electron-microscopic; radicals